Prarancangan Pabrik Akrilonitril Menggunakan Proses Sohio Dengan Disain Alat Utama Kolom Distilasi (D-101) - Daratul Laila; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrylonitrile is a liquid, colorless and soluble in a variety of organic solvents, such as ethanol, ether, acetone, isopropanol, ethyl acetate, carbon tetrachloride and benzene, only partially soluble in water, which is usually used as a precursor in the manufacture of acrylamide and acrylic acid. Dimeseration of acrylonitrile can produce adiponitrile, which is used in the synthesis of polyamides. In small quantities it is used as a fumigant. Acrylonitrile is produced using propylene as raw material and reacted with ammonia and air in a fluidized bed reactor in the presence of a heterogeneous bismuth molybdate catalyst. The by-products produced are HCN, acetonitrile (ACN) and water. The unreacted ammonia is removed with acidified water with sulfuric acid as dilute ammonia sulfate, which can be recovered by crystallization. Propylene, ammonia and oxygen are fed into the reactor, the catalyst used is bismuth molybdate, after mixing it is then fed to the absorption unit, the absorbent material used in this unit is sulfuric acid which is useful for neutralizing excess unreacted ammonia, then fed back to the second absorption. with an absorbent in the form of water. After that proceed to the distillation unit to obtain pure acrylonitrile. The main design is a distillation tower which serves to separate the acrylonitrile from the mixture. The need for acrylonitrile in Indonesia is still imported. With the presence of an acrylonitrile factory in Indonesia, it is expected to reduce the need for imports. If domestic needs have been met, these acrylonitrile products can be exported, thereby increasing industrial development in Indonesia. In addition, the establishment of this factory can create jobs and can trigger new factories that require acrylonitrile products. The type of distillation column used is a tray column. The operating conditions of the distillation column are 103.15 °C at the top and 215.39 °C at the bottom with a pressure of 2 bar each. Factory economic analysis is carried out to determine the feasibility of the factory to be built. Based on the results of the economic feasibility analysis of the factory, the acrylonitrile plant is feasible to build with an IRR of 22.67%, ROI of 59.54% and BEP of 35%. Keywords: acetone, carbon tetrachloride, ethanol, ether, isopropanol.